Intramolecular p-i-n junction photovoltaic device based on selectively doped carbon nanotubes. (February 2017) - Chen, Changxin; Song, Chuanjuan; Yang, Junru; Chen, Dingqiang; Zhu, Wenhuan; Liao, Chenghao; Dong, Xusheng; Liu, Xiaodong; Wei, Liangming; Hu, Nantao; He, Rong; Zhang, Yafei
Abstract: Photovoltaic devices show promising applications in detection and energy fields as well as in next-generation optoelectronic circuits. The use of the ideal photosensitive material and device design are critical for achieving a high-performance photovoltaic device. Here, an intramolecular p-i-n junction photovoltaic device based on selectively doped carbon nanotubes is investigated. In this kind of device, the opposite ends of an individual single-walled carbon nanotube (SWCNT) channel are doped selectively by triethyloxonium hexachloroantimonate (OA) and polyethylene imine (PEI) to obtain stable p- and n- type SWCNT segments respectively, while the middle segment of the SWCNT is kept intrinsic, causing the formation of an intra-tube p-i-n junction for the efficient separation of photogenerated electron-hole pairs. The optical-absorption and electrical testing demonstrate that the OA and PEI can dope the SWCNTs into the stable p- and n- types, respectively. In the dark, the prepared p-i-n junction device behaves as a diode with a high rectification ratio >10 3 that can be tuned by the gate voltage. Under a 1550-nm monochromatic illumination, the device exhibits a good photovoltaic effect with a large open-circuit voltage of 0.41 V and an external power conversion efficiency of ~4.2%. The quantum efficiency of the device is estimated to be as high as ~73%. Graphical abstract: Highlights: A p-i-n junction photovoltaic device based on selectively doped CNTs is investigated. It is demonstrated that the OA and PEI can dope SWCNTs into stable p- and n- type. The devices behave as gate-dependent diodes, with a maximum rectification ratio >10 3 . The devices exhibit good photovoltaic effect with a Voc of 0.41 V and a α of ~73%.